Is increased activation in the fusiform face area to Greebles a result of appropriate expertise training or caused by Greebles' face likeness? - Liu, Kuo; Chen, Chiu-Yueh; Wang, Le-Si; Jo, Hanshin; Kung, Chun-Chia (Frontiers in Neuroscience, 2023)
Background: In 2011, Brants, Wagemans, & Op de Beeck (JOCN 23:12, pp. 3949–3958) trained eight individuals to become Greeble experts, and found neuronal inversion effects [NIEs; i.e., higher Fusiform Face Area (FFA) activity for upright, rather than inverted Greebles]. These effects were also found for faces, both before and after training. By claiming to have replicated the seminal Greeble training study (i.e., Gauthier, Tarr, Anderson, Skudlarski, & Gore, 1999, Nat Neurosci, 2, 568-573), Brants et al. interpreted these results as participants viewing Greebles as faces throughout training, contrary to the original argument of subjects becoming Greeble experts only after training. However, Brants et al.’s claim presents two issues. First, their behavioral training results did not replicate those of Gauthier, Tarr conducted in 1997 and 1998, raising concerns of whether the right training regime had been adopted. Second, both a literature review and meta-analysis of NIEs in the FFA suggest its impotency as an index of face(-like) processing. Objectives: To empirically evaluate these issues, the present study compared two documented training paradigms (i.e., Gauthier & Tarr, 1997, Vision Res, 37, 1673-1682; and Gauthier, Williams, Tarr, & Tanaka, 1998, Vision Res, 38, 2401-2428) and compared their impact on the brain.